KEPASTIAN HUKUM PENYELESAIAN SENGKETA PAJAK PERTAMBAHAN NILAI DALAM TRANSAKSI PENGADAAN BARANG DAN JASA - Nathaniel Prawira,; Khalimi, Khalimi; Achmad Fitrian, (Journal of Innovation Research and Knowledge, 2025)
Value Added Tax (VAT) disputes in goods and services procurement transactions often arise due to differences in interpretation of regulations between taxpayers and tax authorities, causing legal uncertainty. this uncertainty is rooted in the complexity of regulation and implementation of tax policies that are not always aligned with business practices. legal certainty in the resolution of tax disputes should be realized through clearer regulations, effective settlement mechanisms, and certainty in legal decisions, so as to provide legal protection for all parties involved. The type of research used in this research is normative law research through statute approach, case approach, and conceptual approach. The types and sources of legal materials used in the study are divided into three categories, namely primary legal materials, secondary legal materials and tertiary legal materials. To obtain materials relevant to the discussion of this paper, the author uses the technique of collecting legal materials through the study of documents (library research) which is analyzed through a normative approach (descriptive-qualitative) The results showed that the use of civil decisions in tax Court decisions had a wide impact juridically, sociologically, and philosophically. Inaccuracy in the application of legal norms can cause uncertainty and shift taxes from the public to the private sphere. Therefore, strong regulation and legal consistency are needed to keep tax disputes in accordance with the principles of justice and legal certainty and the use of civil judgment considerations in tax cases can challenge legal certainty. Although it gives an additional perspective, this should be in accordance with clear tax regulations. It is necessary to strengthen regulation and synchronization between the tax system and civil law to avoid uncertainty and create a transparent, fair and accountable system.